2014
DOI: 10.1155/2014/786353
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes after Treatment of Periodontal Intrabony Defects with Nanocrystalline Hydroxyapatite (Ostim) or Enamel Matrix Derivatives (Emdogain): A Randomized Controlled Clinical Trial

Abstract: Introduction. Periodontitis is an inflammatory process in response to dental biofilm and leads to periodontal tissue destruction. The aim of this study was the comparison of outcomes using either an enamel matrix derivative (EMD) or a nanocrystalline hydroxyapatite (NHA) in regenerative periodontal therapy after 6 and 12 months. Methods. Using a parallel group, prospective randomized study design, we enrolled 19 patients in each group. The primary outcome was bone fill after 12 months. Attachment gain, probing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…7,136,[156][157][158] The majority of the studies indicate no added benefits in either clinical and radiographic gains when EMD is used with the addition of graft materials. 71,78,109,111,113,114,[119][120][121][122][123][124][152][153][154][155] These updated studies confirmed the conclusions of meta-analyses of RCTs that there are few additional benefits of EMD when used in conjunction with other regenerative materials/approaches 159 (SORT level A). The exceptions are limited reports that indicate that improved PD, CAL, and/or bone fill is achievable when EMD augments the effect of bone grafts 112,131 or bone graft enhances the effects of EMD.…”
Section: Periodontal Regenerative Materials and Approach Bone Replacesupporting
confidence: 67%
See 1 more Smart Citation
“…7,136,[156][157][158] The majority of the studies indicate no added benefits in either clinical and radiographic gains when EMD is used with the addition of graft materials. 71,78,109,111,113,114,[119][120][121][122][123][124][152][153][154][155] These updated studies confirmed the conclusions of meta-analyses of RCTs that there are few additional benefits of EMD when used in conjunction with other regenerative materials/approaches 159 (SORT level A). The exceptions are limited reports that indicate that improved PD, CAL, and/or bone fill is achievable when EMD augments the effect of bone grafts 112,131 or bone graft enhances the effects of EMD.…”
Section: Periodontal Regenerative Materials and Approach Bone Replacesupporting
confidence: 67%
“…There are several studies in which EMD has been used in combined therapy (Table 6). 71,78,109,[111][112][113][114][115][116][119][120][121][122][123][124][130][131][132][152][153][154][155] Histologic evidence of periodontal regeneration has been demonstrated when EMD is used in combination with autogenous bone, a bovine-derived natural bone mineral (NBM), † † bioactive glass, ‡ ‡ NBM + PRP, nanocrystalline hydroxyapatite (NHA), or biphasic calcium phosphate. 7,136,[156][157][158] The majority of the studies indicate no added benefits in either clinical and radiographic gains when EMD is used with the addition of graft materials.…”
Section: Periodontal Regenerative Materials and Approach Bone Replacementioning
confidence: 99%
“…It has been previously shown that inorganic materials (HAp and other calcium phosphates), have been used for periodontal regeneration [4,17,18]. Calcium phosphate has excellent properties including: (1) a similar composition to bone minerals; (2) the ability to form bone apatite-like materials or carbonate HAp; (3) is able to stimulate cells, leading to the formation of bone; and (4) osteoconductivity [32].…”
Section: Discussionmentioning
confidence: 99%
“…These materials should ideally be non-cytotoxic and nanosized, to permit the particles to pass through the tissue. Moreover, nano-sized HAp has been shown to have favorable clinical outcomes for the management of intrabony periodontal defects [17,18]. Due to size effects and surface phenomena at the nanoscale, nanosized biomaterials possess unique properties over its bulk-phase counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale deposits of HA and calcium phosphate create a more complex implant surface for osteogenesis (Goen e et al, 2007). Commercial nanoproducts used to treat bone defects are Ostim ® (Heraeus Kulzer, Hanau, Germany), VITOSSO (Orthovita, Inc, USA and NanOSS™ (Angstrom Medica, USA) (Kumar and Vijayalakshmi, 2006;Machot et al, 2014).…”
Section: Dentristymentioning
confidence: 99%